Pengaruh Pembiayaan Murabahah, Pembiayaan Mudharabah, dan Pembiayaan Musyarakah pada Profitabilitas Bank Perkreditan Rakyat Syariah - Ahmad Sobiyanto; Nur Fatwa (Jurnal Ilmiah Ekonomi Islam, 2023)
This research was conducted to test the effect of sharia financing contracts (Murabaha, Mudharabah, and Musyarakah Financing) on Profitability (ROA) of Harta Insan Karimah Sharia Rural Banks in 2018-2022. The data of Financial Services Authority (OJK) is used as the population with a sample of the financial statements of the Harta Insan Karimah Sharia Rural Bank for the period 2018-2022 (17 samples). The research method in this study is the Ordinary Least Square (OLS) method with quantitative research using multiple linear regression analysis techniques using SPSS version 25 software. The independent variable (X) tested in this study consists of Murabahah, Mudharabah, and Musyarakah Financing. The dependent variable (Y) used in this study is Return on Assets (ROA). The results of the study show that simultaneously, X variables (Murabaha, Mudharabah, and Musyarakah Financing) has no effect on variable Y, namely profitability (ROA) of BPRS Harta Insan Karimah in 2018-2022. Partially, Musyarakah Financing has a positive and significant impact on the profitability (ROA) of Harta Insan Karimah Sharia Rural Banks in 2018–2022, whereas Murabahah Financing and Mudharabah Financing each have a positive and insignificant impact on the Return on Assets (ROA) of BPRS Harta Insan Karimah in 2018–2022.